Decydujący moment. Wokół biografii Andrzeja Bobkowskiego - Nowak, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article consists of two short parts. The first part explores rather theoretical problems chosen by the author during his current work. Among them is the titular problem – the crucial moment in somebody’s life, with all its consequences. The second part contains the opening excerpt from Bobkowski’s biography recently written by the author. According to the researcher, it sets up the biographer’s tone and the whole approach to the subject. This initial part of the upcoming book entitled The Escape is an example of the implementation of the ‘decisive moment’ concept in practice.